City Outdoor Lighting System Control. Problems and Prospects - Andrei Bachurin (Proceedings of the International Conference on Applied Innovations in IT, 2015)
This review describes current problems, trends and prospects of the quasi-automatic light control system. The lighting systems of million cities.